The power of Connections: Evidence from financial companies - Farag, Hisham; Dickinson, David (Journal of Corporate Finance, 2020)
The role of political connections has been highlighted as an important influence on firm behaviour and value. We argue that political connections are just part of a wider pool of connections such as those with regulatory bodies and government officials. Using a quasi-experiment, we provide empirical evidence that broader directors' connections reduce company risk. More specifically, we find a negative and significant relationship between directors with both government and regulatory bodies' connections and company risk. Interestingly, we find that connected female directors are less risk-averse compared with their male counterparts. Our results also reveal that connected directors, though offered generous compensation packages, do not necessarily generate higher stock abnormal performance. Therefore, shareholders of financial companies should consider the trade-off between the incremental costs and benefits of appointing connected directors. The paper provides helpful insights for regulators and wider stakeholder groups.